2012
DOI: 10.1038/labinvest.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1-mediated cell death is increased by CD30-induced signaling in anaplastic large cell lymphoma cells but not in Hodgkin lymphoma cells

Abstract: Endogenous b-galactose-binding lectins have many biological functions, but their biological significance in Hodgkin lymphoma (HL) and anaplastic large cell lymphoma (ALCL) remains unclear. By immunohistochemistry, we analyzed the expression of galectin-1 and galectin-3 in HL and ALCL cases as well as in cell lines, and investigated the pharmacological effects of galectin-1 treatment with and without CD30 pre-stimulation of HL and ALCL cell lines. The galectin-3-negative human embryonic kidney cell line (HEK-29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…For example, the stimulation of the mitochondrial apoptotic pathway by galectin-1 initiated ceramide release and the requirement of prophenoloxidase system for ceramide-induced apoptosis prompted us to investigate the role of the p53 pathway for cell death (Bremer et al, 2006;Hahn et al, 2004). Previously research demonstrated that galectin-1 can induce cell death of T cells and thymocytes, while other groups have shown that galectin-1 can kill B cells, breast cancer cells and prostate cancer cells (Kurushima et al, 2005;Suzuki et al, 2012). Galectins introduces chemotaxis, activation, oxidative activity and degranulation of eosinophils (Bremer et al, 2006;Paz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the stimulation of the mitochondrial apoptotic pathway by galectin-1 initiated ceramide release and the requirement of prophenoloxidase system for ceramide-induced apoptosis prompted us to investigate the role of the p53 pathway for cell death (Bremer et al, 2006;Hahn et al, 2004). Previously research demonstrated that galectin-1 can induce cell death of T cells and thymocytes, while other groups have shown that galectin-1 can kill B cells, breast cancer cells and prostate cancer cells (Kurushima et al, 2005;Suzuki et al, 2012). Galectins introduces chemotaxis, activation, oxidative activity and degranulation of eosinophils (Bremer et al, 2006;Paz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-1 is expressed in anaplastic large cell lymphoma (ALCL) as well as Hodgkin lymphoma (HL) (1). However, the biological significance of galectin-1 still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of LGALS1 have been found in HL patients with advanced stages, and LGALS1 might represent a potential biomarker in HL [208][209][210][211][212][213][214][215]. The protein is expressed by Reed-Sternberg cells and is an important regulator of tumor-immune escape and immune cell homeostasis.…”
Section: Hodgkin Lymphoma and The Immune Responsementioning
confidence: 99%